Become : the five commitments of purposeful leadership - Hannum, Mark (McGraw-Hill, 2020)
"Become a leader worth following by using the proven, evidence-based methods of the widely respected, global leadership firm Linkage, Inc. and leadership development expert Mark Hannum. The world's greatest leaders focus on three critical things: they are committed to accomplishing something that matters; they articulate a vision that others embrace; and they demonstrate a series of five commitments that make up the message of this book. In Become, Mark Hannum, a leading Executive Coach, Consultant, Practitioner and Researcher in the leadership field, reveals the evidence-based secrets that surfaced from vast data Linkage has collected on leadership effectiveness. He details the five commitments that the best leaders make to themselves and their organizations."--Provided by publisher